Trajetórias epistemológicas da geografia: uma análise do conceito de território nos estudos agrários sobre povos e comunidades tradicionais - Silva, João Emerson Cunha (2024)
The history of geography shows that the paths followed by the concept of territory, throughout scientific production in geography, are marked by alternations, while in certain phases of its history the aforementioned concept lost ground to more traditional concepts, in others, it assumed centrality in the development of research in this field of knowledge. With regard to agrarian geography and its relations with the concept of territory, the strengthening of the concept is evident from critical geography studies in the 1970s/1980s and cultural studies, notably from the 1990s onwards, a situation that contrasts with the little space that the concept obtained in the classical and theoreticalquantitative phases of agrarian studies. In this context, the research aims to understand the approaches to the concept of territory in agrarian studies on traditional peoples and communities, using the annals of the International Symposium on Agrarian Geography (2003-2019) as a bibliographical selection. In order to theoretically support the paths to achieving this objective, we base ourselves, in the field of studying the history of geography, on the thoughts of authors such as Claval (2014a), Moreira (2015) and Andrade (2008), already in Regarding the concept of territory, the theoretical contributions are made up of authors such as Haesbaert (2019), Saquet (2020), Almeida (2005) and Andrade (2004). From a methodological perspective, as our research deals directly with texts produced and published in events in the area of geography, we chose to use content analysis, specifically that discussed by Bardin (2022). Finally, we found, within the research results, a wide variety of territorial approaches detected throughout the bibliographical section researched, which total more than a hundred definitions of what constitutes the concept of territory. Furthermore, we saw the strengthening of themes relating to indigenous people and quilombolas, which were expressed by the increase in the number of research on these peoples throughout the SINGA annals.